Interstitial Metamorphoses: Informal Urbanism and the Tourist Gaze. (December 2013) - King, Ross; Dovey, Kim
Marina Warner has argued that it is in the interstices between inconsistent cultures and ideas that creativity and new paradigms—metamorphoses—arise. In cities of the developing world, the most prominent instances of interstitial spaces and practices relate to questions of urban informality. In one sense, informal settlements insert themselves in the cracks and gaps of the formal city; in another sense, there are the frictions where informal space rubs against the formal, with interstitial practices arising in the cracks and gaps that such confrontations produce; informal economies emerge, spaces and practices are intertwined and intersecting. In yet a further sense, informal practices can invade even the most emblematic spaces of state and formal economy. So, a question: where might one seek signs of metamorphosis—new forms of creativity, new ways of thinking, transformation to a different social condition—in these various forms of informal/formal intersections and interstices? We explore this question with regard to public spaces and political events in Bangkok. The argument of this paper is that a new and potentially transformational level of invasion comes with the searing gaze of global media and tourist intrusion.